Refugee camps and livestock: Child malnutrition and health implications in Dadaab Refugee Camp, Kenya - Herrington, Rosie (Jameel Observatory for Food Security Early Action, 2025)
Presented at the Jameel Observatory Community of Practice meeting and drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 13-16 May 2025